The impacts of livestock diseases and their control on growth and development processes that are pro-poor - Perry, Brian D.; Grace, Delia (Royal Society, 2009)
Poverty is now at the heart of development discourse; we discuss how it is measured and understood. We next consider the negative and positive impacts of livestock on pro-poor development. Taking a value-chain approach that includes keepers, users and eaters of livestock, we identify diseases that are road blocks on the ‘three livestock pathways out of poverty’. We discuss livestock impacts on poverty reduction and review attempts to prioritize the livestock diseases relevant to the poor. We make suggestions for metrics that better measure disease impact and show the benefits of more rigorous evaluation before reviewing recent attempts to measure the importance of disease to the poor. High impact of a disease does not guarantee high benefits from its control; other factors must be taken into consideration, including technical feasibility and political desirability. We conclude by considering how we might better understand and exploit the roles of livestock and improved animal health by posing three speculative questions on the impact of livestock diseases and their control on global poverty: how can understanding livestock and poverty links help disease control?; if global poverty reduction was the aim of livestock disease control, how would it differ from the current model?; and how much of the impact of livestock disease on poverty is due to disease control policy rather than disease itself?